LEGAL PRINCIPLES OF STATE CONTROL OVER INTERNATIONAL TRANSFERS OF DUAL-USE GOODS - Sevostianenko, Denys (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2024)
B a c k g r o u n d . The need to control international transfers of dual-use goods remains an urgent need of the entire International Community in the twenty-first century, as such processes are accompanied by the risk of obtaining these goods by international terrorist groups, international criminal organizations and governments of states against which restrictive measures have been introduced. The purpose of the article is to provide a theoretical justification for the administrative and legal model of state control over international transfers of dual-use goods.M e t h o d s . In the course of the study, the author used the general scientific methods of analysis, synthesis, induction, deduction, as well as the formal legal method.R e s u l t s . The analysis of the study, conducted by representatives of the Kyiv School of Economics and the Yermak-McFaul International Working Group, resulted in the identification of the necessary information on the volume of imports by the aggressor state of certain types of dualuse goods, as well as on the routes of supply of such goods. As it turned out, a third of such imported goods were manufactured by companies registered in states that have imposed certain restrictions on such transfers and many of which are parties to the Wassenaar Arrangement. It is worth noting that this agreement does not provide for the exchange of information on transferred dual-use goods (except for those covered by the Sensitive List and the Very Sensitive List). The existence of a provision establishing the need to exchange information on international transfers of all dual-use goods to states that are not parties to the specified export control regime will encourage governments of member states to strengthen national control over international transfers of such goods.C o n c l u s i o n s . Several conclusions and proposals have been developed to improve the regulation of state control over international transfers of dual-use goods. In particular, the need for the Ministry of Foreign Affairs of Ukraine to develop, first, draft amendments to the Wassenaar Arrangement's founding documents to launch the exchange of information between member states on the transfer of all dual-use goods to nonparties to the agreement, and, second, a plan to reach consensus with other member states on the implementation of such amendments.
Keywords: military-technical cooperation, dual-use goods, Wassenaar Arrangement, export control, legal regulation. administrative law, international treaties